Juventude e meio ambiente: pesquisa-ação em educação ambiental realizada no programa Projovem Adolescente de Franca/SP - Bovo, Lúcia Regina Tanaka [UNESP] (2015)
This paper presents environmental education as a tool in the development of citizenship, encompassing more than the transmission of knowledge about the environment. The objective of this work is to expose the perception of young people regarding the environment through environmental education project implemented in Projovem Adolescent Program (National Program for Youth Inclusion) in the city of Franca (SP), researching the feasibility of inclusion of environmental issues in a socio-educational program to arouse the interest of users to recognize the contemporary environmental problems. The theme is included in the daily lives of eighteen participants in the program as a strategy to strengthen the mobilization and social participation. Is justified by the high incidence and aggravation of environmental issues in the past decades in Brazil and worldwide. Participation and preparation of young people whose experience of citizenship enables diagnose, plan and execute actions that can contribute to your benefit and the community in which they live. The method used is action research which is conceived as a practice in which research and action appear as moments of a single process of collective learning